Reconstruction Of Corruption Criminal Acts Law Connectivity In Military Justice: Analysis Of Constitutional Court Decision Number 87/Puu-Xxi/2023 From The Perspective Of Maslahah Mursalah - Siregar, Rais Abdurrahman; Lubis, Fauziah; Tanjung, Dhiauddin (UNIVERSITAS PAKUAN, 2025)
Legal uncertainty regarding jurisdiction in cases of corruption involving civilian and military actors, as well as its impact on the effectiveness of the Corruption Eradication Commission (KPK RI), has caused the KPK RI to hesitate in investigating cases of corruption, which could potentially hinder the optimal handling of cases and harm the constitutional rights of citizens to receive the benefits of development. This study aims to unravel how the military hierarchy structure, military court jurisdiction, and analyze the Constitutional Court (MK) Decision Number 87/PUU-XXI/2023 are carried out through the perspective of Maslahah Mursalah, an Islamic legal philosophy that focuses on public welfare and benefit. These research uses a qualitative method with a legal-normative approach. The research is conducted by reviewing and analyzing relevant literature related to the research topic being studied. The results of the study indicate that the military environment is classified as a social stratification when viewed from a legal sociology perspective, with one of its characteristics being the existence of differences in rank and position within the military hierarchy. Furthermore, progressive law advocates the need to revise the Military Court Act so that military personnel who commit general criminal offenses can be fully tried in civilian courts, which undoubtedly represents a significant step forward toward a more humane and just legal system. Furthermore, an analysis of the Maslahah Mursalah principle regarding the Constitutional Court's Decision No. 87/PUU-XXI/2023, using the criteria outlined by Asy-Syatibi, shows that the Court, in its decision, considered the principle of legal certainty as explained in its legal reasoning, as well as Islamic law governing the principle of legal certainty, thereby ensuring that this decision does not contradict Islamic law.